10,3)

(32)

2

5

-3 -2 -1

1

3

4 5

-2

DR

Or

A

y = -3x + 3

B

y=-{x+3

С

y = 3x -

D

y = 3x - 3

(32)

2

5

-3 -2 -1

1

3

4 5

-2

DR

Or

A

y = -3x + 3

B

y=-{x+3

С

y = 3x -

D

y = 3x - 3

Asked
6 months ago

Viewed
226334 times

**Answer:**

the equation is y=-1/3x+3

Enter your username or email to reset your password. You will receive an email with instructions on how to reset your password. If you are experiencing problems resetting your password contact us or send us an email